2010
DOI: 10.1115/1.4002595
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Mechanism of Heat Transfer Augmentation in Stagnating Flows Subject to Freestream Turbulence

Abstract: Experiments have been performed in a water tunnel facility to examine the physical mechanism of heat transfer augmentation by freestream turbulence in classical Hiemenz flow. A unique experimental approach to studying the problem is developed and demonstrated herein. Time-resolved digital particle image velocimetry (TRDPIV) and a new variety of thin-film heat flux sensor called the heat flux array (HFA) are used simultaneously to measure the spatiotemporal influence of coherent structures on the heat transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…Properties of the generated turbulence were calculated from the measured flow field with no stagnation model present at downstream distances 17.5M and the results compared well with the published correlations (Baines & Peterson 1951). These calculations were performed using the methods described by Gifford et al (2011). Details of the grid geometry and turbulence properties are given in table 1.…”
Section: Water Tunnel Facility and Turbulence Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Properties of the generated turbulence were calculated from the measured flow field with no stagnation model present at downstream distances 17.5M and the results compared well with the published correlations (Baines & Peterson 1951). These calculations were performed using the methods described by Gifford et al (2011). Details of the grid geometry and turbulence properties are given in table 1.…”
Section: Water Tunnel Facility and Turbulence Generationmentioning
confidence: 99%
“…Gifford, Diller & Vlachos (2011) used timeresolved digital particle image velocimetry (TRDPIV) and a thin-film heat flux sensor to study heat transfer augmentation in the stagnation region of a flow containing large-scale free-stream turbulence. Subsequent tracking of the vortices present showed that the rate of heat transfer at the wall was directly influenced by the strength and proximity of the vortex.…”
Section: Introductionmentioning
confidence: 99%
“…The circulation (Γ) was calculated around iso-contours of the swirling strength. The vortextracking algorithm described previously (Gifford, 2011) was used to compile the trajectory of each vortex.…”
Section: Identification and Tracking Of Coherent Structuresmentioning
confidence: 99%
“…Over the years a number of investigators [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] have studied the influence on turbulence on laminar boundary layer development and transition and their work support the conclusion that turbulence level, turbulence scale, and Reynolds number have significant influences. Mayle [24] discussed the influence of turbulence combined with favorable and adverse pressure gradient on spot production.…”
Section: Introductionmentioning
confidence: 92%